Effectiveness of vesicoamniotic shunt in fetuses with congenital lower urinary tract obstruction: an updated systematic review and meta‐analysis. (June 2017) - Nassr, A. A.; Shazly, S. A. M.; Abdelmagied, A. M.; Araujo Júnior, E.; Tonni, G.; Kilby, M. D.; Ruano, R.
ABSTRACT: Objective: To evaluate the effect on perinatal and postnatal survival of vesicoamniotic shunt (VAS) as treatment for fetal lower urinary tract obstruction (LUTO). Methods: An electronic search of Ovid MEDLINE, Ovid EMBASE, Ovid Cochrane Central Register of Controlled Trials, Ovid Cochrane Database of Systematic Reviews and Scopus using relevant search terms was conducted from inception to June 2015 to identify studies comparing outcomes of VAS vs conservative management for treatment of LUTO. Cohort studies and clinical trials were considered eligible. Single‐arm studies and studies that did not report survival were excluded. Sample size and language were not criteria for exclusion. Two reviewers extracted independently data in a standardized form, including study characteristics and results. Primary outcomes were perinatal and postnatal survival. Secondary outcome was postnatal renal function. Data on fetal survival were expressed as odds ratio (OR) and 95% CI. Results: Of the 423 abstracts retrieved, nine studies were eligible for inclusion. These studies included 112 fetuses treated with VAS and 134 that were managed conservatively. There was heterogeneity in study design. Although the data demonstrated a difference in effect estimates between the study arms in terms of perinatal survival (OR, 2.54 (95% CI, 1.14–5.67)), there was no difference in 6–12‐month survival (OR, 1.77 (95% CI, 0.25–12.71)) or 2‐year survival (OR, 1.81 (95% CI, 0.09–38.03)). In addition, there was no difference in effect on postnatal renal function between fetuses that underwent intervention and those that did not (OR, 2.09 (95% CI, 0.74–5.94)). Conclusions: Available data seem to support an advantage for perinatal survival in fetuses treated with VAS compared with conservative management. However, 1–2‐year survival and outcome of renal function after VAS procedure remain uncertain. Further studies are necessary to evaluate the effectiveness of fetal intervention for LUTO based on different severity of the disease, due to the very low quality of the studies according to GRADE guidelines. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.